Innovative Behavior in Russian Business-Organizations: Theoretical and Methodological Foundations of Empirical Research - A G Effendiev; P S Sorokin (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The article presents the framework of empirical research into individual innovative behavior in Russian business-organizations. On the basis of the analysis of contemporary world literature and the results of empirical research of social aspects of business innovations the authors put forward a hypothesis that innovation-related processes are interrelated on the micro-, mezzo-, and macro-levels. On the one hand, the innovative development of business and the creation of useful innovations result from the individual activity of the employees. On the other hand, the social macromedia is the key factor, determining the innovative efficiency not only of business organizations, but of society as a whole.